Cancer outcomes are independent of preoperative CA 19‐9 in anatomically resectable pancreatic ductal adenocarcinoma: A retrospective cohort analysis. Issue 6 (16th July 2020) - Kim, Joon Kyung; DePeralta, Danielle K.; Ogami, Takuya; Denbo, Jason W.; Pimiento, Jose; Hodul, Pamela J.; Malafa, Mokenge P.; Kim, Dae W.; Fleming, Jason B.; Powers, Benjamin D.
Abstract: Background and Objectives: Current guidelines recommend neoadjuvant therapy for pancreatic ductal adenocarcinoma (PDAC) patients with anatomically resectable tumors but elevated CA 19‐9. However, this recommendation is based on data from anatomically resectable and borderline resectable PDAC patients. Therefore, we analyzed the association of preoperative CA 19‐9 with oncologic outcomes in a cohort of anatomically resectable PDAC patients. Methods: A single‐institution PDAC database from 2007 to 2015 included patients who underwent guideline‐based staging and were anatomically resectable. Patients with bilirubin above 1.5 after decompression, nonsecretors of CA 19‐9, and borderline resectable patients were excluded. Statistical analysis included frequency testing and regression modeling for recurrence and survival. Results: One hundred forty‐four PDAC patients were identified; 16 (11.1%) had elevated preoperative CA 19‐9 ≥ 1000. A CA 19‐9 level ≥1000 was not associated with demographic, clinical, or pathological factors. After adjustment for potential confounders, CA 19‐9 levels (continuous, median, 500 U/mL, or 1000 U/mL cut‐offs) were not associated with recurrence or overall survival (OS). Conclusions: Although guidelines recommend CA 19‐9 to determine the management of anatomically resectable PDAC patients, CA 19‐9 was not associated with recurrence or OS in this cohort. Our findings do not suggest that CA 19‐9 alone should determine the PDAC treatment strategy.